Association of Human Leukocyte Antigen Class 1 genes with Stevens Johnson Syndrome with severe ocular complications in an Indian population. Issue 1 (December 2017) - Kannabiran, Chitra; Ueta, Mayumi; Sangwan, Virender; Rathi, Varsha; Basu, Sayan; Tokunaga, Katsushi; Kinoshita, Shigeru
Abstract Stevens Johnson syndrome (SJS) is part of a spectrum of adverse drug reactions resulting in the destruction of skin, mucous membranes, and the ocular surface. A similar, more severe form of the disorder included in this spectrum is toxic epidermal necrolysis (TEN). Approximately 35% of patients suffer chronic sequelae such as vascularization, corneal scarring, conjunctival inversion to the cornea, keratinization, symblepharon, scarring of the palpebral conjunctiva, trichiasis, and severe dry eye. We focused on 80 Indian patients with SJS/TEN with severe ocular complications (SOC) and investigated the association of alleles atHLA -A, HLA-B andHLA-C loci; the controls were 50 healthy Indian volunteers. Genotyping atHLA-A, HLA-B, andHLA-C loci showed a significant positive association withHLA-A*33:03, HLA-B*44:03, andHLA-C*07:01 alleles, and a significant negative association withHLA-B*57:01 andHLA-C*06:02 . This indicates thatHLA-A*33:03, HLA-B*44:03 andHLA-C*07:01 are risk alleles, andHLA-B*57:01 andHLA-C*06:02 are protective alleles in this population. We also found that the haplotypes consisting ofHLA-B*44:03 andHLA-C*07:01 were strongly associated with SJS/TEN with SOC in our Indian population (p = 1.1 × 10−7, odds ratio = 11.0). Describing the association of the haplotype could facilitate the understanding of increased risk factors for developing SJS/TEN with SOC.